Digitalisasi Sistem Absensi dan Informasi Karyawan di Perusahaan BJIB - Femmy Johan; Jennifer Verty; Novan Wijaya (MDP Student Conference, 2026)
BJIB still uses manual attendance, which can lead to potential recording errors, delays in recapitulation, and a lack of transparency in attendance data. This study aims to design and build a mobile-based employee service application that supports digital attendance using QR Codes and provides information in the form of employee data and attendance history. This study uses the waterfall method, which includes needs analysis, interface design, implementation using Laravel and MySQL, testing, and maintenance. Testing was carried out on the login feature, attendance entry and exit, and history display. The results of the study show that all features run well and are able to record attendance accurately and present data in real-time. This system improves administrative efficiency, reduces human error, and accelerates the recapitulation process. Thus, the developed application can be an effective solution for BJIB in supporting the digitalization of employee data management.